2009
DOI: 10.1097/pec.0b013e3181a34144
|View full text |Cite
|
Sign up to set email alerts
|

Parental Preference for Rehydration Method for Children in the Emergency Department

Abstract: When given the opportunity to make an informed decision, more parents chose intravenous rehydration. However, the prospect of an effective oral antiemetic medication might lead more parents to choose oral rehydration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 18 publications
0
31
0
2
Order By: Relevance
“…However, less within-country variability in the type of IV or NG rehydration was observed, suggesting an influence of training and health care organization, specific to each country, on physician practices [9]. Hoekstra in Australia and New-Zealand [11], and Karpas in Canada [12], have also shown differences in practice after ORS failure in different hospitals within the same country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, less within-country variability in the type of IV or NG rehydration was observed, suggesting an influence of training and health care organization, specific to each country, on physician practices [9]. Hoekstra in Australia and New-Zealand [11], and Karpas in Canada [12], have also shown differences in practice after ORS failure in different hospitals within the same country.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a real risk/benefit assessment of the widespread use of ondansetron in AGE in Europe is still lacking. Studies have shown that parents prefer IV rehydration [12] and treatments that shorten diarrhea duration [15]. With respect to health care providers, another recent study indicated that only 14% of physicians favor NG over IV rehydration [16].…”
Section: Discussionmentioning
confidence: 99%
“…However, physicians have often resisted administering ORT, believing it to be time-consuming and a drain on clinical resources [37]. One study surveyed parents who were educated on oral versus intravenous rehydration and found that nearly twice as many parents chose the intravenous method when given a choice [38 ]. Following treatment, however, another study showed that parents' satisfaction is much greater with oral versus intravenous rehydration [39].…”
Section: Enteral Versus Parenteral Fluid Resuscitationmentioning
confidence: 97%
“…The latter is significant because, when given the opportunity to decide, 62% of caregivers chose intravenous rehydration over ORT. 30 However, the availability of an effective, orally administered antiemetic might make them choose ORT instead. 30 Dehydration has been identified as the most common diagnosis resulting in ED revisits, as well as revisits requiring hospitalization.…”
Section: Figurementioning
confidence: 99%
“…30 However, the availability of an effective, orally administered antiemetic might make them choose ORT instead. 30 Dehydration has been identified as the most common diagnosis resulting in ED revisits, as well as revisits requiring hospitalization. 31 However, this fact is underrecognized by health care providers.…”
Section: Figurementioning
confidence: 99%